CMLHS researchers shine at CITREX 2012 - Ahmad, Ibrahim; Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
30 March 2012. “They reap what they sow.” Kudos to all CMLHS research teams who participated in the Creation, Innovation, Technology and Research Exposition Competition (CITREX 2012), organized by the Research & Innovation Department and Students Affairs & Alumni Department, UMP. CITREX 2012, which was held at the UMP Sports Complex from 26 to 28 March 2012, showcased 130 research products from UMP associates and students of various faculties and centers. Three research teams represented CMLHS, and all three won Gold Medals for their research products.